Is real exchange rate misalignment a leading indicator of currency crises in Nigeria? - Babatunde S. Omotosho (CBN Journal of Applied Statistics, 2015)
This paper constructs an early warning system for currency crises in Nigeria based on selected key macroeconomic indicators. It estimates the probabilities of currency crises as a logistic function of the included variables within the framework of a logit model. Particularly, the extent to which real exchange rate misalignment (RERMIS) could be used as a leading indicator of currency crisis is investigated by including its lag in the model. Our findings show that the likelihood of currency crisis increases when the real exchange rate is misaligned; the exchange rate is volatile; oil price declines; debt/GDP ratio increases; and the current account balance to GDP ratio declines. The study confirms that RERMIS represents a useful leading indicator of currency crisis in the country. The paper therefore recommends regular assessment of the Naira exchange rate vis-à-vis its equilibrium level with a view to implementing appropriate policy responses to rein in or avoid prolonged and substantial misalignments. Since all the variables enter the equation in their one period lags, the estimated model constitutes a reliable early warning system to policy makers on the possibility of impending currency crisis in the country.
Keywords: C33; F31; F41; 330; Real exchange rate misalignment; exchange market pressure; currency crises; logit model